2020
DOI: 10.1088/1742-6596/1538/1/012110
|View full text |Cite
|
Sign up to set email alerts
|

The development of mathematical problem based on Higher Order Thinking Skill (HOTS) on comparative material by implementing PBL and its effect on the teacher’s creative thinking skill

Abstract: Assessing both learning process and achievement is a pedagogical competency in which it refers to an ability that must be possessed by the teacher. The learning done by teacher is intended to maximize the students’ higher order thinking skills, that is why the assessment is required to measure their higher order thinking skills. This research was carried out to study the teacher’s creative thinking skill and the implementation of problem-based learning to improve teacher’s creative thinking skill in creating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…This is also supported by similar research that critical thinking is the first step for students to think creatively which is classified as HOTS (Susilowati & Sumaji, 2020). However, previous studies have shown that teachers have difficulties on how to teach HOTS and developing HOTS-based assessments (FitzPatrick & Schulz, 2010;Schulz & Fitzpatrick, 2016;Widiatsih et al, 2020). On the other hand, teachers should familiarize students with solving mathematical problems through an assessment in the form of a mathematical numeracy test that can use four approaches, namely assessment of validity, reliability, level of difficulty, and discrimination power (Annisavitri et al, 2020).…”
mentioning
confidence: 58%
“…This is also supported by similar research that critical thinking is the first step for students to think creatively which is classified as HOTS (Susilowati & Sumaji, 2020). However, previous studies have shown that teachers have difficulties on how to teach HOTS and developing HOTS-based assessments (FitzPatrick & Schulz, 2010;Schulz & Fitzpatrick, 2016;Widiatsih et al, 2020). On the other hand, teachers should familiarize students with solving mathematical problems through an assessment in the form of a mathematical numeracy test that can use four approaches, namely assessment of validity, reliability, level of difficulty, and discrimination power (Annisavitri et al, 2020).…”
mentioning
confidence: 58%
“…According to Widiatsih et al (2020) there are still many teachers who still do not understand and master how to compose questions, the characteristics of HOTS questions and how to make ordinary questions into HOTS questions. It is important to train teachers to develop questions that are included in HOTS.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers must be involved in the thought process when determining the learning process and compiling mathematics assessments [27]. Furthermore, teachers must have competencies that include the ability to conduct assessments, both on the learning process and student learning outcomes based on the applied curriculum [28]. In mathematics, giving assessments in the form of problem solving or multiple representation tasks can improve students' cognitive processes where the assessments create space for reflection and analysis of the problems given [29], [30].…”
Section: Introductionmentioning
confidence: 99%